EFFICIENT REGENERATION LOCAL BANANA TISSUE CULTURE USING FLORAL APICES BY CYTOKININ COMBINATION - Makhsunah, Isnina Tasya; Habibi, Ali Mukit; Khofifa, Rendryana Aulia Nur; Ubaidillah, Mohammad (BRIN - Badan Riset dan Inovasi Nasional, 2023)
Banana (Musa sp.) is an important crop that is widely cultivated and consumed in Indonesia. Banana plants production can be increased through tissue culture with the use of explants and the right combination of hormones. This study was conducted to determine the use of flower apices explants on local banana varieties using a combination of cytokinin hormones containing BAP (Benzylaminopurine) and several levels of TDZ (Thidiazuron). The result of this research was analyzed using a one-way analysis of variance. The hormone combination in this study consists of MS + BAP 2 mg/L + three concentrations of TDZ (2 mg/L, 2.5 mg/L, and 3 mg/L) as a regeneration medium. Three local banana varieties (Kepok Putih, Kepok Kuning, and Pisang Susu) was cultured on the three combination medium. The results showed that the use of flower apices explants contained in banana flowers grown on MS media with a combination of cytokinin hormones could increase the efficiency of explant regeneration. Media MS + BAP 2 mg/L + TDZ 3 mg/L gave the best regeneration rate for Kepok Putih (62.50%), Kepok Kuning (62.50%) and Banana Susu (56.25%) compared to TDZ 2. mg/L and TDZ 3 mg/L. The novelty of this study can provide information in the propagation of local banana plants using flower apices explants.